2005
DOI: 10.1080/09674845.2005.11732679
|View full text |Cite
|
Sign up to set email alerts
|

Progressive decrease of proinsulin secretion in sulphonylurea-treated type 2 diabetes

Abstract: Progressive deterioration of beta-cell function is proposed as a disease-related factor of sulphonylurea (SU) failure in type 2 diabetes. If it gradually worsens over time then disease duration may mirror the progressive beta-cell deterioration. The aim of the present study is to assess whether or not disease duration is influential in remodelling the secretion pattern of insulin-like molecules and in glucose control of SU-treated type 2 diabetes. A research model is used to investigate proinsulin secreting ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Increasing duration predicted reduced likelihood of 6‐month glimepiride response [36] and two studies found a relationship between duration of disease and the response to glucose challenge. Among SU‐treated patients, total proinsulin levels and intact proinsulin values were significantly greater after glucose challenge for patients with disease duration less than 5 years compared with those with disease duration of at least 5 years, but the specific insulin response did not differ between duration groups [37]. In the other study, high responders to nateglinide therapy had a shorter disease duration than low responders [20].…”
mentioning
confidence: 77%
“…Increasing duration predicted reduced likelihood of 6‐month glimepiride response [36] and two studies found a relationship between duration of disease and the response to glucose challenge. Among SU‐treated patients, total proinsulin levels and intact proinsulin values were significantly greater after glucose challenge for patients with disease duration less than 5 years compared with those with disease duration of at least 5 years, but the specific insulin response did not differ between duration groups [37]. In the other study, high responders to nateglinide therapy had a shorter disease duration than low responders [20].…”
mentioning
confidence: 77%